Ranking of multivariate populations a permutation approach with applications - Corain, Livio; Arboretti, Rosa; Bonnini, Stefano (CRC Press/Taylor & Francis Group, 2016)
Ranking of Multivariate Populations: A Permutation Approach with Applications presents a novel permutation-based nonparametric approach for ranking several multivariate populations. Using data collected from both experimental and observation studies, it covers some of the most useful designs widely applied in research and industry investigations, such as multivariate analysis of variance (MANOVA) and multivariate randomized complete block (MRCB) designs